2007
DOI: 10.1210/jc.2007-0531
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Expression of the Glycerol Channel Aquaporin-7 Gene Is Altered in Severe Obesity But Not in Type 2 Diabetes

Abstract: Expression of AQP7 is down-regulated in women with severe obesity. The expression of this glycerol channel is not affected by type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 15 publications
5
51
0
2
Order By: Relevance
“…The G264V AQP7 variant had previously been screened in Japanese and Caucasian subjects with obesity and/ or type 2 diabetes, but no association between the genotype and these phenotypes could be demonstrated. 20,21 These studies did not include measurement of the urine glycerol levels, but normal plasma glycerol levels were reported for the homozygous carrier in the Japanese study, 20 in line with the findings in our study.…”
Section: Genetic Screening For Aqp3 Aqp7 and Aqp9supporting
confidence: 88%
See 1 more Smart Citation
“…The G264V AQP7 variant had previously been screened in Japanese and Caucasian subjects with obesity and/ or type 2 diabetes, but no association between the genotype and these phenotypes could be demonstrated. 20,21 These studies did not include measurement of the urine glycerol levels, but normal plasma glycerol levels were reported for the homozygous carrier in the Japanese study, 20 in line with the findings in our study.…”
Section: Genetic Screening For Aqp3 Aqp7 and Aqp9supporting
confidence: 88%
“…Another study found the G264V AQP7 heterozygous variant in 8% of a Caucasian population (in contrast to 3.75% in the Japanese population), but again no association was found with obesity or diabetes. 21 This later study showed that AQP7 was downregulated in subcutaneous adipose tissue of women with severe obesity but without type 2 diabetes. It was recently suggested that AQP3 and AQP9 represent additional pathways for transport of glycerol in human adipocytes and that these AQPs are therefore potentially responsible for AQP7 redundancy.…”
Section: Introductionmentioning
confidence: 97%
“…33 Expression of the AQP7 gene is reduced in obese women, and polymorphisms of this gene are associated with obesity and diabetes. 34,35 Not only may a decrease in sugar intake and a reduction in glycemic index improve insulin resistance in humans, but feeding C. elegans with glucose may also be able to function as an animal model of insulin resistance based upon the cited studies with aquaporin. For example, an elevated glycemic index with a 2% glucose diet may offer a possibility to observe an increase in lifespan of C. elegans using drugs that effectively reduce insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The expression and regulation of Aqp7 and Aqp9 in rodents have been extensively addressed, but results of gene expression in humans are scarce [15,[22][23][24]. To test the hypothesis that coordinated regulation of the two tissuespecific glycerol channels is important in morbid obesity and glucose homeostasis, gene expression levels of AQP7 in VAT and AQP9 in liver were studied in a wellcharacterized group of volunteers including lean (LN) and obese (OB) women.…”
Section: Introductionmentioning
confidence: 99%